Analyzing The Role Of 'Sanak Indonesia Madani' As Tourism Counselor In Enhancing Community-Based Tourism Hr Quality In West Sumatra - Aulia, Lailatul; Malihah, Elly; Andari, Rini (UNIVERSITAS PAKUAN, 2023)
Community-based tourism (CBT) is one of the leading tourism concepts in Indonesia currently that carries the concept of from community, by community, and for community. It is hoped that tourism will no longer only focus on profit, but also will provide benefits to the community in order to improve their welfare. One of the provinces in Indonesia that has also adapted the CBT concept is West Sumatra. Currently there are as many as 238 Tourism Villages that already have decrees from the government. So the Sanak Nan Salapan was formed as a team of tourism councelor to help the community empowerment. Consisting eight member that are not only tourism practioner, but also those engaged in the arts and creative economy. In this study, the authors wanted to analyze the role and strategies that have been carried out by Sanak Nan Salapan in empowering the community, and CBT field. The research approach was carried out in a qualitative descriptive manner by interviewing the Sanak Nan Salapan team and also gain information needed from their official Instagram account @sanaknansalapan. After almost two years of providing guidance, training and assistance to the community, it turns out that the problems that arise are still from the readiness, mindset and mentality of the tourism actors themselves. It is quite difficult to find new pioneers who are able to independently develop the CBT concept in their village, therefor the assistance must continue.